The Impact of Picky Eating Behavior on Nutritional Status in Toddlers Aged 24-59 Months Using Weight and Height Measurements at Bone Health Center, Muna Regency - Murni Sahida, Wa Ode Siti; Azizi Jayadipraja, Erwin; Kartini, Kartini (Waluya The International Science of Health Journal, 2024)
Introduction: One of the Health Centers in Muna Regency, namely Bone Health Center, has 1.6% very thin toddlers, 7.4% thin toddlers, 0.5% very short toddlers, 5.7% short toddlers, 6.4% malnourished toddlers, 8.7% undernourished toddlers, 0.2% obese toddlers. Eating problems in children, one of which is picky eating which is a factor influencing the nutritional status of children. Generally, in children who behave picky, or choose food, there will be inadequacy of food intake. Based on this background, researchers are interested in conducting research on the relationship between picky eating behavior and nutritional status in toddlers aged 24-59 years based on Weight/Height at the Bone Health Center, Muna Regency Method: Using quantitative research methods with a cross-sectional approach, the population was 566 and the sample was 228 toddlers aged 24-59 months using the Lameshow formula in determining the sample. Data collection by interview using a questionnaire. Result: X2 count is .468 < X2 table is 3.841, so there is no relationship between picky eating and nutritional status based on Weight/Height in the Bone Health Center area, Muna Regency. Conclusion: The Health Center as a health service provider should increase outreach to the community and maximize monitoring and improvement of nutrition together with parents of toddlers, especially in the Bone Health Center area.